Following hearts, one cell at a time: recent applications of single-cell RNA sequencing to the understanding of heart disease. Issue 1 (December 2018) - Ackers-Johnson, Matthew; Tan, Wilson; Foo, Roger
Abstract The mammalian heart contains heterogeneous cell types contributing to pathological changes in cardiac disease. In this Comment, we explore how single-cell transcriptomic approaches are unveiling intricate cellular mechanisms and gene co-expression networks that regulate the workings, and failings, of the heart.